Designing a Business Application for Workflows in Cloud Computing - Chawla, Ravneet Kaur (My University, 2012)
Cloud computing is a new benchmark towards enterprise application development that can effectively facilitate the execution of workflows in business process management system. The workflow technology can manage the business processes efficiently satisfying the requirements of modern enterprises. A description of a business process is required in the form of a workflow specification to deploy the process as a workflow-based enterprise application. To run a workflow application, workflow management software is required which includes a process editor to support the design of workflow models. Workflows in context of software development are used to rapidly develop the software application improving the software quality. The part of the thesis work involves the design of a workflow for an online banking application in an open-source workflow system, YAWL (Yet another Workflow Language).With its built-in verification facility, it analyzes and validates the workflow specification according to the YAWL schema. The work also involves how the same workflow specification can be designed in the process perspective of a visual modelling development environment, Orangescape Studio that itself runs as a cloud application. The application with its four-tiered architecture is built on REST-style service interface. The application built can be deployed on some of the major cloud infrastructures offered by Google, Microsoft and IBM.
me, CSED
Keywords: Cloud Computing; Workflow; WFMS; YAWL